Hollow fiber membrane and its manufacturing method
The development of a hollow fiber membrane with a dense polyethersulfone layer and controlled void diameters addresses the limitations of conventional membranes, achieving enhanced separation performance and mechanical strength.
Patent Information
- Application Number
- JP2021111281
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-05
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-07-05
AI Technical Summary
Conventional hollow fiber membranes lack sufficient separation performance and mechanical strength, and often contain macrovoids that compromise their effectiveness.
A hollow fiber membrane with a dense layer containing polyethersulfone, where the diameter of the voids in the dense layer is 10 μm or less, and the dense layer is not located on the outer surface, is produced using a spinning method with a specific viscosity range and coagulation conditions.
The resulting hollow fiber membrane exhibits excellent separation performance and mechanical strength, with no macrovoids, making it suitable for applications such as ultrafiltration.
Smart Images

Figure 0007659457000003 
Figure 0007659457000004 
Figure 0007659457000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a hollow fiber membrane and a method for producing the same. [Background technology]
[0002] In recent years, most households are increasingly drinking less water directly from the tap, and are instead using commercially available water filled in plastic bottles, tap water filtered through a water purifier, etc. Although the initial cost of purchasing a water purifier is high, for the reasons (1) to (3) below, water purifiers are used as low-cost devices that are kind to people and the environment. (1) Water treatment costs will be lower, given that large volumes of water can be purified over a long period of time; (2) Unlike plastic bottles, the containers do not generate waste after use. (3) There is no need to carry heavy loads, as would be the case if you were to purchase commercially available plastic bottles at a store. The water purifier has a hollow fiber membrane for the purpose of removing viruses, bacteria, particles, etc.
[0003] A hollow fiber membrane is produced by spinning a membrane-forming solution containing a polymer. As a polymer contained in the membrane-forming solution, polyethersulfone has attracted attention. Patent documents 1 and 2 disclose examples of producing a hollow fiber membrane using a membrane-forming solution containing polyethersulfone as a polymer. Patent document 3 discloses a porous hollow fiber membrane containing a polysulfone-based polymer and a hydrophilic polymer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2016-505363 [Patent Document 2] JP 2007-136449 A [Patent Document 3] International Publication No. 2016 / 113964 Summary of the Invention [Problem to be solved by the invention]
[0005] There has been a demand for a hollow fiber membrane that is free of macrovoids and has better separation performance and mechanical strength than conventional hollow fiber membranes. The present invention has been made in view of the above circumstances, and provides a hollow fiber membrane that is free of macrovoids and has better separation performance and mechanical strength. [Means for solving the problem]
[0006] The embodiments of the present invention are as follows. [1] A hollow fiber membrane having a dense layer containing polyethersulfone, wherein the diameter of voids in the dense layer is 10 μm or less. [2] The hollow fiber membrane according to the above [1], wherein the dense layer is not located on the outer surface of the hollow fiber membrane. [3] The hollow fiber membrane according to the above [1] or [2], wherein the polyethersulfone has a weight average molecular weight of 50,000 to 80,000. [4] The hollow fiber membrane according to any one of [1] to [3] above, wherein the hollow fiber membrane is a hollow fiber membrane for ultrafiltration. [5] A method for producing a hollow fiber membrane having a dense layer with voids having a diameter of 10 μm or less, comprising a spinning step of using a membrane-forming dope containing polyethersulfone and dimethylsulfoxide and having a viscosity of 7 to 10 Pa s at 25°C. [6] In the spinning step, the membrane-forming solution is extruded into a coagulation bath to perform spinning, The method for producing a hollow fiber membrane according to the above-mentioned [5], wherein the coagulation bath contains water and the content of an organic solvent in the coagulation bath is 1% by weight or less. [7] The method for producing a hollow fiber membrane according to [5] or [6] above, wherein the dense layer is not located on the outer surface of the hollow fiber membrane. [8] The method for producing a hollow fiber membrane according to any one of the above [5] to [7], wherein the polyethersulfone has a weight average molecular weight of 50,000 to 80,000. [9] The method for producing a hollow fiber membrane according to any one of [5] to [8] above, wherein the hollow fiber membrane is a hollow fiber membrane for ultrafiltration. Effect of the Invention
[0007] It is possible to provide a hollow fiber membrane that is free of macrovoids and has excellent separation performance and mechanical strength. [Brief description of the drawings]
[0008] [Figure 1] 1 is an SEM photograph of a cross section of a hollow fiber membrane washed in an autoclave at 110° C. using water as a core liquid in Example 1. [Diagram 2] FIG. 2 is a graph showing the separation performance of the hollow fiber membrane washed in an autoclave at a temperature of 105° C. in Example 1. [Diagram 3] FIG. 2 is a graph showing the separation performance of the hollow fiber membrane washed in an autoclave at a temperature of 110° C. in Example 1. [Figure 4] FIG. 2 is a graph showing the separation performance of the hollow fiber membrane washed in an autoclave at a temperature of 121° C. in Example 1. [Diagram 5] FIG. 2 is a graph showing the separation performance of the hollow fiber membranes prepared in Comparative Examples 1 to 3. [Figure 6] 1 is an SEM photograph of a cross section of the hollow fiber membrane produced in Comparative Example 1. [Figure 7] 1 is an SEM photograph of a cross section of the hollow fiber membrane produced in Comparative Example 2. [Figure 8] 1 is an SEM photograph of a cross section of the hollow fiber membrane produced in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (Hollow fiber membrane) The hollow fiber membrane of the present invention has a dense layer containing polyethersulfone, and the diameter of the voids in the dense layer is 10 μm or less. The dense layer constituting the hollow fiber membrane does not have macrovoids consisting of voids with a diameter exceeding 10 μm in its cross section. Therefore, the hollow fiber membrane can have excellent separation performance for objects to be removed such as viruses, bacteria, and particles. In addition, since there are no macrovoids in the dense layer, the actual membrane thickness is thick, and the hollow fiber membrane can have excellent mechanical strength such as tensile strength and pressure resistance. The diameter of the voids in the dense layer is measured as follows. First, a SEM image of the cross section of the hollow fiber membrane taken in advance is captured using a microscope VHX-5000 (System ver.1.04) manufactured by Keyence Corporation. Next, the diameter of the voids in the dense layer is measured using the automatic area measurement function of the image processing of the microscope VHX-5000. The diameter of at least 500 voids in the dense layer is measured as described above, and if the largest diameter of the measured voids is 10 μm or less, it can be determined that "the diameter of the voids in the dense layer is 10 μm or less." If the shape of the void is not circular, the length of the longest part of the void is determined to be the diameter of the void and the diameter is measured.
[0010] The position of the dense layer in the hollow fiber membrane is not particularly limited, but it is preferable that the dense layer is not located on the outer surface of the hollow fiber membrane. Since the dense layer is not located on the outer surface of the hollow fiber membrane, the dense layer is not exposed to the outside, so that the dense layer is prevented from being damaged during the production and use of the hollow fiber membrane, and the separation performance and mechanical strength of the hollow fiber membrane can be maintained at excellent levels for a long period of time. The dense layer may be present on the inner surface of the hollow fiber membrane, or inside between the inner and outer surfaces, and it is preferable that the dense layer is present in a part other than the outer surface of the hollow fiber membrane. In addition, when the dense layer is present at a specific position in the cross section of the hollow fiber membrane, the dense layer can be visually confirmed as a region without macrovoids in an SEM image of the cross section of the hollow fiber membrane or in the cross section of the actual hollow fiber membrane.
[0011] Polyethersulfone is a highly safe material, the use of which is not strictly regulated in each country. The weight-average molecular weight of polyethersulfone is preferably 50,000 to 80,000, more preferably 60,000 to 70,000. By having the weight-average molecular weight of polyethersulfone within the above range, the viscosity of the membrane-forming solution can be increased to promote the formation of a dense layer. As a result, a dense layer having better separation performance can be obtained. The weight-average molecular weight of polyethersulfone can be measured by GPC (Gel Permeation Chromatography). The polyethersulfone is not particularly limited, but VERADEL (registered trademark) 3000MP manufactured by Solvay Specialty Polymers Japan Co., Ltd. can be mentioned.
[0012] The hollow fiber membrane of the present invention can be used for various purposes in various fields, for example, the hollow fiber membrane can be used as a membrane for a water purifier, an industrial separation membrane, or a humidification membrane for a fuel cell. The hollow fiber membrane of the present invention is preferably a hollow fiber membrane for ultrafiltration. The hollow fiber membrane of the present invention has a dense layer, and since there are no macrovoids in the dense layer, it can have excellent separation performance. For example, the hollow fiber membrane for ultrafiltration of the present invention can be used for removing bacteria and viruses, separating proteins and enzymes, performing artificial dialysis, removing trace substances, etc.
[0013] (Method of manufacturing hollow fiber membrane) The method for producing a hollow fiber membrane with a dense layer of the present invention includes a step of spinning a membrane-forming solution containing polyethersulfone and dimethylsulfoxide and having a viscosity of 7 to 10 Pa·s at 25°C. The diameter of the voids in the dense layer is 10 μm or less. The use of polyethersulfone and dimethylsulfoxide is not strictly regulated in any country, and they are highly safe materials. By having the viscosity of the membrane-forming solution within these ranges, a hollow fiber membrane with a dense layer having excellent separation performance can be formed.
[0014] In one embodiment of the method for producing a hollow fiber membrane, a hollow fiber membrane is produced by a nonsolvent induced phase separation method (NIPS). More specifically, after preparing a membrane dope, the membrane dope is extruded directly or by free running from the outer tube of a hollow fiber spinning nozzle having a double ring structure into a coagulation bath, and at the same time, a core liquid that is incompatible with the membrane dope is extruded from the inner tube of the hollow fiber spinning nozzle to perform spinning to obtain a filament. In this case, the coagulation bath preferably contains water, and the content of the organic solvent in the coagulation bath is 1% by weight or less. The filament thus obtained is washed in an autoclave as necessary, and then dried in an oven to obtain a hollow fiber membrane. The temperature of the autoclave during washing of the filament is not particularly limited, but can be set to a temperature of, for example, 100 to 130°C. The drying conditions of the hollow fiber membrane are not particularly limited as long as the hollow fiber membrane is sufficiently dried, but for example, it is preferable to perform drying at 20 to 80°C, preferably 25 to 60°C, for 0.5 to 4 hours.
[0015] In the hollow fiber membrane manufacturing method of the present invention, it is considered that a dense layer without macrovoids is manufactured as follows. That is, in the hollow fiber membrane manufactured by the non-solvent induced phase separation method, an internal structure is formed based on the phase separation phenomenon of the membrane-forming solution. In the conventional hollow fiber membrane, the solvent diffuses and flows out of the membrane-forming solution in a liquid-liquid demixing system (the moment the membrane-forming solution enters the coagulation bath, the solvent of the membrane-forming solution is exchanged with the non-solvent of the coagulation bath, and the structure of the hollow fiber membrane is fixed), which generates macrovoids. In contrast, in the hollow fiber membrane manufacturing method of the present invention, a high-viscosity membrane-forming stock solution with a viscosity of 7 to 10 Pa·s is used, so the exchange between the solvent of the membrane-forming solution and the non-solvent of the coagulation bath is delayed, and it is considered that a start-delayed demixing system (a state in which the structure of the hollow fiber membrane is not instantly fixed even after the membrane-forming solution enters the coagulation bath, and phase separation proceeds) is formed. It is believed that the solvent diffused from the membrane-forming solution and became less likely to flow out, which delayed the fixation of the hollow fiber membrane structure in the coagulation bath, and as a result, the formation of the hollow fiber membrane structure continued even after the membrane-forming solution entered the coagulation bath, resulting in no macrovoids.
[0016] At least dimethyl sulfoxide is used as a solvent for the membrane-forming solution. The membrane-forming solution may contain ethylene glycol, polyvinylpyrrolidone, and the like in addition to dimethyl sulfoxide. By containing ethylene glycol in the membrane-forming solution, the viscosity of the membrane-forming solution can be increased and the internal structure of the hollow fiber membrane can be controlled. In addition, by containing polyvinylpyrrolidone in the membrane-forming solution, hydrophilicity is imparted to the hollow fiber membrane and the viscosity of the membrane-forming solution can be increased to control the internal structure of the hollow fiber membrane.
[0017] The core liquid of the membrane-forming solution and the coagulation bath may be a solvent incompatible with polyethersulfone, such as dimethylacetamide, ethylene glycol, water, etc. The temperatures of the core liquid and the coagulation bath are not particularly limited, but are preferably −20 to 60° C., more preferably 0 to 30° C., in order to stably form a membrane. EXAMPLES
[0018] Preferred embodiments of the present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to these examples.
[0019] Example 1 A homogeneous membrane-forming stock solution was prepared at room temperature from 17 parts by weight of polyethersulfone (VERADEL (registered trademark) 3000MP manufactured by Solvay Specialty Polymers Japan Co., Ltd.; weight average molecular weight Mw is 64,000 to 68,000), 4 parts by weight of ethylene glycol (manufactured by Kanto Chemical Co., Ltd.; first-class), 10 parts by weight of polyvinylpyrrolidone, and 69 parts by weight of dimethyl sulfoxide. The viscosity of the prepared membrane-forming stock solution at 25°C was measured with a viscometer manufactured by A&D Co., Ltd. (product name: SV-10A) and found to be 7.5 Pa·s. This membrane-forming stock solution and a core liquid consisting of water or a 20% by weight aqueous solution of dimethyl sulfoxide were extruded through a double annular nozzle into a water coagulation bath and subjected to dry-wet spinning to obtain a filamentous material. The obtained filament was then washed in an autoclave at 105°C, 110°C, or 121°C for 1 hour, and then dried in an oven at 40°C to obtain a porous polyethersulfone hollow fiber membrane with an outer diameter of 350 μm and an inner diameter of 250 μm. FIG. 1 is a SEM (Scanning Electron Microscope) photograph of the cross section of a porous polyethersulfone hollow fiber membrane obtained by washing the obtained filament in an autoclave at a temperature of 110°C using water as the core liquid. The upper and lower figures in FIG. 1 show SEM photographs of the cross section at magnifications of 200 times and 2000 times, respectively. As shown in FIG. 1, no macrovoids were present in the cross section of the porous polyethersulfone hollow fiber membrane obtained in Example 1. More specifically, the above SEM photograph was captured using a microscope VHX-5000 (System ver.1.04) manufactured by Keyence Corporation, and the diameters of all voids (more than 500 voids) in the SEM photograph were measured using the automatic area measurement function of the image processing. As a result, it was confirmed that the maximum diameter among the diameters of the measured voids was 1.2 μm, which was 10 μm or less. In addition, a dense layer was visually confirmed between the vicinity of the outer surface and the inner surface in the cross section of the porous polyethersulfone hollow fiber membrane.Similarly, the diameter of the voids in the dense layer was measured for the porous polyethersulfone hollow fiber membranes obtained when the membranes were washed in an autoclave at temperatures of 105° C. and 121° C. using water as the core liquid, and when the membranes were washed in an autoclave at temperatures of 105° C., 110° C., and 121° C. using a 20% by weight aqueous solution of dimethyl sulfoxide as the core liquid. As a result, the maximum diameter among the diameters of the voids measured was 1.6 μm for the hollow fiber membrane washed in an autoclave at 105° C. using a 20% by weight aqueous solution of dimethyl sulfoxide as the core liquid, 1.4 μm for the hollow fiber membrane washed in an autoclave at 110° C., and 1.2 μm for the hollow fiber membrane washed in an autoclave at 121° C., all of which were 10 μm or less. No macrovoids were present in the cross section of the dense layer, and a dense layer was confirmed between the vicinity of the outer surface and the inner surface. In addition, the maximum diameter of the measured voids was 1.0 μm for the hollow fiber membrane washed at 105°C in an autoclave using water as the core liquid, and 0.9 μm for the hollow fiber membrane washed at 121°C in an autoclave, both of which were less than 10 μm.No macrovoids were present in the cross section of the dense layer, and a dense layer was confirmed between the vicinity of the outer surface and the inner surface.
[0020] Comparative Example 1 A homogeneous membrane-forming solution consisting of 17 parts by weight of polyethersulfone (E1010 (registered trademark) manufactured by BASF Japan Ltd.), 10 parts by weight of polyvinylpyrrolidone, and 73 parts by weight of dimethyl sulfoxide was prepared at room temperature. The viscosity of the prepared membrane-forming solution at 25°C was measured using a viscometer manufactured by A&D Co., Ltd. (product name: SV-10A) and found to be 2.5 Pa·s. This membrane-forming solution and a core liquid consisting of water were extruded through a double annular nozzle into a water coagulation bath to perform dry-wet spinning to obtain a filament. The obtained filament was then washed in an autoclave at a temperature of 121°C for 1 hour and then dried in an oven at 40°C to obtain a porous polyethersulfone hollow fiber membrane with an outer diameter of 345 μm and an inner diameter of 190 μm. 6 is a SEM (Scanning Electron Microscope) photograph of the cross section of the porous polyethersulfone hollow fiber membrane of Comparative Example 1 obtained by using water as the core liquid and washing the obtained filamentous material in an autoclave at a temperature of 121° C. When the diameter of the voids in the SEM photograph was measured in the same manner as in Example 1, it was confirmed that the maximum diameter of the voids measured in the cross section of the porous polyethersulfone hollow fiber membrane obtained in Comparative Example 1 was 56 μm, and that macrovoids consisting of voids having a diameter exceeding 10 μm were present. As a result, it was confirmed that voids exceeding 10 μm were present in the cross section of the porous polyethersulfone hollow fiber membrane of Comparative Example 1.
[0021] Comparative Example 2 A homogeneous membrane-forming solution consisting of 17 parts by weight of polyethersulfone (E1010 (registered trademark) manufactured by BASF Japan Ltd.), 10 parts by weight of polyvinylpyrrolidone, and 73 parts by weight of dimethylsulfoxide was prepared at room temperature. The viscosity of the prepared membrane-forming solution at 25°C was measured using a viscometer manufactured by A&D Co., Ltd. (product name: SV-10A), and was found to be 2.5 Pa·s. This membrane-forming solution and a core liquid consisting of a 20% by weight aqueous solution of dimethylsulfoxide were extruded through a double annular nozzle into a water coagulation bath and subjected to dry-wet spinning to obtain a filament. The obtained filament was then washed in an autoclave at a temperature of 121°C for 1 hour and then dried in an oven at 40°C to obtain a porous polyethersulfone hollow fiber membrane with an outer diameter of 355 μm and an inner diameter of 205 μm. 7 is a SEM (Scanning Electron Microscope) photograph of the cross section of the porous polyethersulfone hollow fiber membrane of Comparative Example 2 obtained by using a 20% by weight aqueous solution of dimethyl sulfoxide as the core liquid and washing the obtained filamentous material in an autoclave at a temperature of 121° C. When the diameter of the voids in the SEM photograph was measured in the same manner as in Example 1, it was confirmed that the maximum diameter of the voids measured in the cross section of the porous polyethersulfone hollow fiber membrane obtained in Comparative Example 2 was 58 μm, and that macrovoids consisting of voids exceeding 10 μm were present. As a result, it was confirmed that voids exceeding 10 μm were present in the cross section of the porous polyethersulfone hollow fiber membrane of Comparative Example 2.
[0022] Comparative Example 3 A homogeneous membrane-forming solution consisting of 17 parts by weight of polyethersulfone (E1010 (registered trademark) manufactured by BASF Japan Ltd.), 10 parts by weight of polyvinylpyrrolidone, and 73 parts by weight of dimethylsulfoxide was prepared at room temperature. The viscosity of the prepared membrane-forming solution at 25°C was measured using a viscometer manufactured by A&D Co., Ltd. (product name: SV-10A), and was found to be 2.5 Pa·s. This membrane-forming solution and a core liquid consisting of a 30% by weight aqueous solution of dimethylsulfoxide were extruded through a double annular nozzle into a water coagulation bath and subjected to dry-wet spinning to obtain a filament. The obtained filament was then washed in an autoclave at a temperature of 121°C for 1 hour and then dried in an oven at 40°C to obtain a porous polyethersulfone hollow fiber membrane with an outer diameter of 375 μm and an inner diameter of 240 μm. 8 is a SEM (Scanning Electron Microscope) photograph of the cross section of the porous polyethersulfone hollow fiber membrane of Comparative Example 3 obtained by using a 30 wt% dimethyl sulfoxide aqueous solution as the core liquid and washing the obtained filamentous material in an autoclave at a temperature of 121 ° C. When the diameter of the voids in the SEM photograph was measured in the same manner as in Example 1, it was confirmed that the maximum diameter of the voids measured in the cross section of the porous polyethersulfone hollow fiber membrane obtained in Comparative Example 3 was 68 μm, and that macrovoids consisting of voids exceeding 10 μm were present. As a result, it was confirmed that voids exceeding 10 μm were present in the cross section of the porous polyethersulfone hollow fiber membrane of Comparative Example 3.
[0023] The pure water permeation rate, separation performance, tensile stress at break, and tensile elongation at break were measured for each of the porous polyethersulfone hollow fiber membranes obtained in Example 1. In addition, the pure water permeation rate, separation performance, tensile stress at break, and tensile elongation at break were measured for each of the porous polyethersulfone hollow fiber membranes obtained in Comparative Examples 1 to 3. The measurement methods for each evaluation item are described below.
[0024] (Pure water permeation rate) The eight looped porous polyethersulfone hollow fiber membranes were placed in a polyvinyl chloride pipe with an outer diameter of 8 mm, an inner diameter of 6 mm, and a length of 75 mm. A hollow fiber membrane module was produced by adhering approximately 10 mm portions of the porous polyethersulfone hollow fiber membranes located at both ends of the polyvinyl chloride pipe to the polyvinyl chloride pipe with epoxy resin. Ion-exchanged water (25°C) was passed through the loop side of the porous polyethersulfone hollow fiber membrane under a pressure of 100 kPag to measure the water permeation rate of the porous polyethersulfone hollow fiber membrane. The measured water permeation rate was then divided by the membrane area of the porous polyethersulfone hollow fiber membrane and the time (hours) for the pure water to pass through to obtain the pure water permeation rate. The pure water permeation rate of each of the porous polyethersulfone hollow fiber membranes obtained in Example 1 is shown in Table 1, and the pure water permeation rate of each of the porous polyethersulfone hollow fiber membranes obtained in Comparative Examples 1 to 3 is shown in Table 2.
[0025] (separation performance) A vinyl chloride pipe with an outer diameter of 8 mm, an inner diameter of 6 mm, and a length of 75 mm was attached to both ends of a clean joint union tee manufactured by Nitta Corporation. Eight porous polyethersulfone hollow fiber membranes were inserted into the vinyl chloride pipe, and 5 to 10 mm portions of the porous polyethersulfone hollow fiber membranes located at both ends of the vinyl chloride pipe were attached to the vinyl chloride pipe with epoxy resin. Urethane resin was further filled on the epoxy resin at one end of the vinyl chloride pipe. A polyethylene glycol solution (a solution containing 0.4 wt% of polyethylene glycols with molecular weights of 40,000 or 70,000, 20,000, 6,000, and 1,000) was passed through the porous polyethersulfone hollow fiber membrane located at the end side filled with urethane resin to perform cross-flow filtration (inlet pressure 100 kPag, outlet pressure 0 kPag). The filtrate was sampled 10 minutes after the start of cross-flow filtration and analyzed by GPC. The rejection rate (%) of polyethylene glycols with each molecular weight was calculated using the following formula. Rejection rate (%) = {1-(peak height in filtrate) / (peak height in blank)} x 100 The measurement results of the separation performance of each of the porous polyethersulfone hollow fiber membranes obtained in Example 1 and Comparative Examples 1 to 3 are shown in Figures 2 to 5. Figures 2 to 4 show the separation performance of the porous polyethersulfone hollow fiber membrane of Example 1 washed at autoclave temperatures of 105°C, 110°C, and 121°C, respectively, and Figure 5 shows the separation performance of the porous polyethersulfone hollow fiber membranes obtained in Comparative Examples 1 to 3.
[0026] (Tensile test) The porous polyethersulfone hollow fiber membrane was attached between the chucks of a tensile tester (load cell ION type manufactured by LLOYD INSTRUMENTS) with a gauge length of 50 mm, and pulled at a test speed of 240 mm / min to determine the tensile breaking load and tensile breaking elongation. The tensile breaking load was divided by the membrane cross-sectional area of the porous polyethersulfone hollow fiber membrane to calculate the tensile breaking stress. The measurement results of the tensile test for each of the porous polyethersulfone hollow fiber membranes obtained in Example 1 are shown in Table 1. The measurement results of the tensile test for each of the porous polyethersulfone hollow fiber membranes obtained in Comparative Examples 1 to 3 are shown in Table 2.
[0027] [Table 1] [Table 2]
[0028] From the results of Tables 1 and 2, it can be seen that the porous polyethersulfone hollow fiber membrane obtained in Example 1 has a high tensile stress at break of 9.0 MPa or more and a high tensile elongation at break of 30% or more, and has mechanical properties superior to those of the porous polyethersulfone hollow fiber membranes of Comparative Examples 1 to 3. In addition, from the results of Figures 2 to 5, the porous polyethersulfone hollow fiber membrane obtained in Example 1 showed a high rejection rate in all cases where water and a 20% by weight aqueous solution of dimethyl sulfoxide were used as the core liquid and the autoclave temperature was set to 105°C, 110°C, and 121°C. Therefore, it was confirmed that the porous polyethersulfone hollow fiber membrane obtained in Example 1 does not have macrovoids and has excellent separation performance and mechanical strength. In addition, some of the porous polyethersulfone hollow fiber membranes of Comparative Examples 1 to 3 showed relatively high rejection rates but had poor mechanical properties.
Claims
1. A dense layer containing polyethersulfone, the diameter of voids in the dense layer being 10 μm or less, A hollow fiber membrane that does not have macrovoids consisting of voids having a diameter greater than 10 μm.
2. 2. The hollow fiber membrane according to claim 1, wherein the dense layer is not located on an outer surface of the hollow fiber membrane.
3. The hollow fiber membrane according to claim 1 or 2, wherein the weight average molecular weight of the polyethersulfone is 50,000 to 80,000.
4. The hollow fiber membrane according to claim 1 , wherein the hollow fiber membrane is an ultrafiltration hollow fiber membrane.
5. A method for producing a hollow fiber membrane having a dense layer with voids having a diameter of 10 μm or less, the method comprising a step of spinning a membrane-forming dope containing polyethersulfone and dimethylsulfoxide and having a viscosity of 7 to 10 Pa·s at 25°C.
6. In the spinning step, the membrane-forming solution is extruded into a coagulation bath to perform spinning, The method for producing a hollow fiber membrane according to claim 5 , wherein the coagulation bath contains water, and the content of an organic solvent in the coagulation bath is 1% by weight or less.
7. The method for producing a hollow fiber membrane according to claim 5 or 6, wherein the dense layer is not located on an outer surface of the hollow fiber membrane.
8. The method for producing a hollow fiber membrane according to any one of claims 5 to 7, wherein the polyethersulfone has a weight average molecular weight of 50,000 to 80,000.
9. The method for producing a hollow fiber membrane according to any one of claims 5 to 8, wherein the hollow fiber membrane is a hollow fiber membrane for ultrafiltration.
Citation Information
Patent Citations
Hollow fiber gas separation composite membrane and preparation method thereof
CN111298664A
Apparatus for counting number of wafers
JP1991023647A
Ultrafiltration membrane, manufacturing method of the same, and using method of ultrafiltration membrane
JP2007136449A
Polymer resin composition for manufacturing microfiltration membrane or ultrafiltration membrane, method for manufacturing polymer filtration membrane, and polymer filtration membrane
JP2016505363A
Highly permeable polyethersulfone hollow fiber membranes for gas separation
US6017474A